2023
DOI: 10.1039/d3gc00442b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-amino-substituted benzothiadiazine oxides by a palladium-catalysed cascade reaction

Abstract: A variety of 3-amino-substituted benzothiadiazine oxides were synthesised in a single-step by applying a palladium-catalysed cascade reaction of 2-azido sulfoximines with isonitriles. The desired heterocycles were observed in good to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 68 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…By applying literature‐known conditions, compound 3 aa was treated with HCl to test the viability of the envisaged dealkylation path (Scheme 4). [18,19a] To our delight, the desired free amine 6 a could be obtained in 74% yield. As by‐product, however, demethylated product 7 a was formed in 10% yield.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…By applying literature‐known conditions, compound 3 aa was treated with HCl to test the viability of the envisaged dealkylation path (Scheme 4). [18,19a] To our delight, the desired free amine 6 a could be obtained in 74% yield. As by‐product, however, demethylated product 7 a was formed in 10% yield.…”
Section: Methodsmentioning
confidence: 96%
“…As part of our ongoing research on the synthesis of sulfur‐containing heterocycles, [19] we recently reported a highly efficient protocol for the synthesis of 3‐amino‐substituted benzothiadiazine oxides [19a] . When applying tetrakis(triphenylphosphine) palladium(0) in catalyst loadings of 0.25–1.5 mol%, 2‐azidosulfoximines reacted with isocyanides to the corresponding heterocycles under ambient conditions and in short reaction times.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfur–nitrogen bonds are ubiquitous in nature, and they play a vital role in medicinal and pharmacological chemistry due to their fascinating bioactive properties. 1,2 N -Acylsulfenamides, 3 a class of compounds featuring S–N bonds, are widely utilized in agrochemicals (captan and phaltan) and polymer applications. Recently, these compounds have received significant interest in medicinal chemistry because of their potential applicability as prodrugs for N–H acid compounds such as amides, carbamates, and ureas (Scheme 1).…”
mentioning
confidence: 99%